Exposure to secondhand tobacco smoke among tertiary institution students of APA Local Government Area of Benue State Nigeria: A menace to future dilemma of Cigarette Complications - Onyemocho, Audu; Aje, Anejo-Okopi Joseph; Johnbull, Ogboi Sonny; Peter, Mbaave Tsavyange; Joseph, Igbudu Terhemen (Archives of Business Research, 2015)
Abstract Background: Nigeria is one of the top ten countries in low and middle income countries where young adults are more exposed to secondhand smoke but the tobacco control policy is inadequate. This study assessed the prevalence and the correlates of secondhand smoke among young educated elites of APA local government area of Benue State, Nigeria. Materials and Methods: A cross-sectional study was carried out during the youth annual week programme with the team entitled “ingredients of a successful career “from 4th -8th January 2014. Inclusion was strictly based on the membership of the local government council elite youth association. Structured self-administered questionnaire was employed. Information obtained includes: Socio-demographic information; cigarrete smoking and pattern of exposure to tobacco smoke in the previous 30 days before the survey. Data was analyzed using SPSS version 20.0. Multiple logistic regressions were performed to test relationship between the predictor variables and the outcome variable (secondhand smoke), by controlling for possible cofounders. Results: The mean age of the educated elites was 25.8years (SD=±5.8 years), 84(20.7%) had history of smoking in the past, while 55 (13.6%) are currently smoking. Forty- three percent of respondents were aware of the harmful effects of SHS on their health. Overall, 49.0% of them were exposed to SHS at Bars/restaurants, 25.2%) % in football viewing centre, and 11.5% in the home. Marital status, religion, and respondents past and current smoking status were among the significant determinates, whereas, parental and close friends smoking status were not significant (p=0.118 and p=0.236 respectively). Conclusion: Our results show that prevalence of SHS exposure was highest in public places. These findings underscore the need for enactment of comprehensive smoke-free legislation and implementation of educational strategies to reduce SHS exposure in homes. Keywords: Secondhand Tobacco Smoke, educated elites, correlates, Benue, Nigeria.